青年期女子の人体計測地値による体水分量の推定 - 増田, 隆; 今井, 克己; 宇部, 一 (日本生理人類学会誌, 1999)
In this paper, a prediction equation for total body water (TBW) from various anthropometric measurements was estabilished. Fifty-four healthy Japanese young women, aged 18 to 20 years, participated in this study. Anthropometric measurements were made of the waist, abdomen, hip, upper arm and thigh circumference, triceps, sub-scapular, abdomen, suprailiac and thigh skinfold thickness, body weight and height. TBW was measured by deuterium oxide (D_2O) dilution method. A step-wise multiple regression analysis of the data indicated that TBW could be predicted from body weight, suprailiac skinfold and abdominal circumference. A step-wise multiple regression analysis gave an equation which yielded a multiple R=0.930 between the predicted TBW and the actual TBW as determined by D_2O dilution method. The standard error of estimete was 1.095 l.